2022
DOI: 10.14218/jcth.2022.00191
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Prognostic Model for Hepatocellular Carcinoma Based on Bioinformatics and the Role of NR6A1 in the Progression of HCC

Abstract: Background and Aims: Generally acceptable prognostic models for hepatocellular carcinoma (HCC) are not available. This study aimed to establish a prognostic model for HCC by identifying immune-related differentially expressed genes (IR-DEGs) and to investigate the potential role of NR6A1 in the progression of HCC. Methods: Bioinformatics analysis using The Cancer Genome Atlas and ImmPort databases was used to identify IR-DEGs. Lasso Cox regression and multivariate Cox regression analysis were used to establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
2
1
0
Order By: Relevance
“…In HCC, NR6A1 was identified as a prognostic marker, and associated with sorafenib resistance in HCC patients 27 . Lin et al showed that NR6A1 might inhibit the HCC immune response 28 and activate the WNT signaling pathway as well as MTOR-signaling pathway 29 , which were similar to our study. On the other hand, NR6A1 could enhance HCC proliferation and invasion in vitro and vivo 29 , which indicated that NR6A1 showed promise as a novel immune therapeutic target for HCC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In HCC, NR6A1 was identified as a prognostic marker, and associated with sorafenib resistance in HCC patients 27 . Lin et al showed that NR6A1 might inhibit the HCC immune response 28 and activate the WNT signaling pathway as well as MTOR-signaling pathway 29 , which were similar to our study. On the other hand, NR6A1 could enhance HCC proliferation and invasion in vitro and vivo 29 , which indicated that NR6A1 showed promise as a novel immune therapeutic target for HCC.…”
Section: Discussionsupporting
confidence: 92%
“…Lin et al showed that NR6A1 might inhibit the HCC immune response 28 and activate the WNT signaling pathway as well as MTOR-signaling pathway 29 , which were similar to our study. On the other hand, NR6A1 could enhance HCC proliferation and invasion in vitro and vivo 29 , which indicated that NR6A1 showed promise as a novel immune therapeutic target for HCC. OSBP2 was first served as a cytosolic protein 30 , and had a high affinity for oxysterols 31 .…”
Section: Discussionsupporting
confidence: 92%
“…DGE (Differential gene expression) analysis was performed on the whole dataset, and 36 PC genes were identified to be differentially expressed from ML identified genes (Figure 3(F)) . After that using lasso penalized coz regression analysis theses 55 PC genes were reduced to 13 genes SEMA3F [51], B4GALNT1 [7], COLEC10 [52], CEP131 [53], APLN [54], GBA [55], SCAMP3 [56], TOMM40L [57], PYGO2 [58] and PLVAP [59] has been reported in literature while CAPN11, SPTY2D1OS and C14orf180 is not so far has been studied in LIHC. Additionally, these 13 genes from survival analysis predicted to be prognostic genes for OS of LIHC cases.…”
Section: Discussionmentioning
confidence: 99%